2019
DOI: 10.1002/jca.21710
|View full text |Cite
|
Sign up to set email alerts
|

Survival of a Jehovah's Witness with thrombotic thrombocytopenic purpura without using plasma: A case report and review of the literature

Abstract: Acquired thrombotic thrombocytopenic purpura (aTTP) is a serious disorder with arteriolar and capillary thrombosis for which the treatment usually requires plasma exchange with plasma as the replacement fluid. Management of patients who do not accept blood products is a serious challenge. We present the case of a Jehovah's Witness patient who achieved clinical response after treatment with plasma exchange using human albumin solution as the replacing fluid, high dose corticosteroids, and rituximab. The patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…4 We summarized nine refractory or relapsed TTP cases in Table 2 after Eskazan's report, who were unresponsive to rituximab and then transferred to bortezomib treatments. [3][4][5][6][7][8][9] Putting these cases together with ours, 25 patients with relapsed or refractory TTP were treated with bortezomib. The age distribution of these patients ranged from 5 to 76 years, suggesting that bortezomib could be used not only in adult, but also in the elderly 10 and children.…”
Section: Bortezomib a Promising Alternative For Patients With Refract...mentioning
confidence: 65%
“…4 We summarized nine refractory or relapsed TTP cases in Table 2 after Eskazan's report, who were unresponsive to rituximab and then transferred to bortezomib treatments. [3][4][5][6][7][8][9] Putting these cases together with ours, 25 patients with relapsed or refractory TTP were treated with bortezomib. The age distribution of these patients ranged from 5 to 76 years, suggesting that bortezomib could be used not only in adult, but also in the elderly 10 and children.…”
Section: Bortezomib a Promising Alternative For Patients With Refract...mentioning
confidence: 65%
“…PLEX is initiated urgently to remove or dilute the ADAMTS13 inhibitor autoantibodies, replace deficient ADAMTS13 enzyme, and regulate the size of vWF multimers to diminish thrombotic risk [14]. While PLEX is the cornerstone of TTP management, studies have reported remissions in patients treated without PLEX [9,10,15,16]. These populations, predominantly comprised of Jehovah's Witnesses, received other therapeutic interventions such as plasmapheresis with albumin rather than plasma replacement, corticosteroids, rituximab, other chemotherapeutic agents, and most recently the anti-vWF nanobody caplacizumab.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, there are several experiences with different therapeutic approaches that demonstrates the non‐criticality of plasma usage. For Jehovah's Witness who refuse PEX therapy, interesting results 10,15‐19 have been achieved with the use of albumin or other proteins, or employing caplacizumab and immunosuppression 19 . In the Hercules trial, in which caplacizumab added to the standard PEX + steroids treatment was compared with standard treatment alone, 43% of pts.…”
Section: Discussionmentioning
confidence: 99%